Modulation of Fear Extinction by Stress, Stress Hormones and Estradiol: A Review - Stockhorst, Ursula; Antov, Martin I. (Frontiers in Behavioral Neuroscience, 2016)
Fear acquisition and extinction are valid models for the etiology and treatment of anxiety, trauma- and stressor-related disorders. These disorders are assumed to involve aversive learning under acute and/or chronic stress. Importantly, fear conditioning and stress share common neuronal circuits. The stress response involves multiple changes interacting in a time-dependent manner: (a) the fast first-wave stress response (with central actions of noradrenaline, dopamine, serotonin, corticotropin-releasing hormone, plus increased sympathetic tone and peripheral catecholamine release) and (b) the second-wave stress response (with peripheral release of glucocorticoids after activation of the hypothalamus-pituitary-adrenocortical axis). Control of fear during extinction is also sensitive to these stress-response mediators. In the present review, we will thus examine current animal and human data, addressing the role of stress and single stress-response mediators for successful acquisition, consolidation and recall of fear extinction. We report studies using pharmacological manipulations targeting a number of stress-related neurotransmitters and neuromodulators (monoamines, opioids, endocannabinoids, neuropeptide Y, oxytocin, glucocorticoids) and behavioral stress induction. As anxiety, trauma- and stressor-related disorders are more common in women, recent research focuses on female sex hormones and identifies a potential role for estradiol in fear extinction. We will thus summarize animal and human data on the role of estradiol and explore possible interactions with stress or stress-response mediators in extinction. This also aims at identifying time-windows of enhanced (or reduced) sensitivity for fear extinction, and thus also for successful exposure therapy.